596 TARGETING GRK2 TO PREVENT AORTIC VALVE CALCIFICATION. (15th December 2022) - Rusciano, Maria Rosaria; Sorriento, Daniela; Valerio, Vincenza; Toni, Anna Laura; Toni, Anna Laura; Di Pietro, Paola; Carrizzo, Albino; Iaccarino, Guido; Poggio, Paolo; Vecchione, Carmine; Ciccarelli, Michele
Abstract: Introduction: Calcific aortic valve stenosis (CAVS) is a clinically relevant issue due to the lack of drugs for prevention or treatment. CAVS is driven by endothelial dysfunction and inflammation. A novel therapeutic strategy should target specific molecules involved in the regulation of both endothelial function and immune responses. G protein-coupled receptor kinase 2 (GRK2) regulates desensitization and downregulation of G protein-coupled receptors, and is able to interact with an extensive repertoire of proteins. We previously demonstrated that the lack of this protein in the endothelium promotes vascular inflammation and atherosclerosis in mice due to increased mitochondrial reactive oxygen species (ROS). Aim: This study aimed to evaluate the role of GRK2 in Aortic Valve Calcification (AVC) by in vivo and in vitro studies. Methods: To reach our purpose we first evaluated the expression of GRK2 in aortic valve of patient displaying fibrotic or calcific lesions of valve leaflets. Then, we evaluated GRK2 expression in mitochondria fraction from EC isolated from CAVS patients (VEC) vs control ECs upon Angiotensin II (AngII) stimulation (1µM). We also performed histological analysis by using 12 months old mice with selective endothelial knock-out of GRK2 (Tie2CRE-GRK2fl/fl) compared to control (GRK2fl/fl) to evaluate the presence of microcalcification in the aortic valve. Finally, we cloned a small sequence of the PH domain of ßARKct into the pcDNA3 to induce GRK2 localization into mitochondria. Results: Immunofluorescence staining of aortic valve leaflets revealed that GRK2expression is more abundant in calcific lesion instead of fibrotic valve. In vitro, we observed that AngII is able to upregulate GRK2 mitochondrial localization in a time-dependent manner in ECs. Otherwise in VEC the stimulation with Ang II is not able to further induce GRK2 mitochondrial localization. Histological analysis revealed that Tie2CRE-GRK2fl/fl mice of 12 months-old display presence of microcalcification, more pronounced than GRK2fl/fl thus demonstrating that the lack of GRK2 in the EC accelerates the calcific degeneration of the aortic valve in mice. Finally, we cloned several small sequences of the PH domain of ßARKct into the pcDNA3.1 plasmid, named as PH#1-4. We found that the transfection into HEK293 cells of the PH#3 potently increased GRK2 localization into the mitochondria as compared to ßARKct, PH4, and pcDNA3.1 as control. PH3 also determined increased biogenesis and reduced ROS production after AngII stimulation. These data support the concept that a smaller portion of the PH domain of ßARKct can reproduce its biological effect Conclusions: In conclusion, our data suggest a direct involvement of GRK2 in the pathogenesis of CAVS. Intracellular re-localization of GRK2 could be a novel strategy to prevent AVC in a pathophysiological condition such as ageing